KEMARAHAN MENURUT KITAB AMSAL DAN KEHARMONISAN PERNIKAHAN PEMIMPIN GEREJA - Jahja, Sundoro (P3M STT Kristus Alfa Omega, 2019)
Abstract The purpose of this study was to determine the effect of couples understanding of anger based on the Book of Proverbs towards of marriage the leader of the Bethel Tabernacle Church of Christ Alfa Omega (GBT KAO) in the Central Java Region. The respondents of this study were 150 GBT KAO leader couples in Jepara, Pati, Semarang, Temanggung, Salatiga and Solo. Based on the correlational test using the Pearson formula, the correlation coefficient is 0.417 with a significance (P-Value) of 0,000. This states that there is a positive and strong influence between the understanding of the couples about anger based on the book of proverbs on the harmony of the marriage of the leader of the Bethel Tabernacle Church of Christ Alfa Omega in the Central Java region. The regression results between variables X and Y can also be seen that the magnitude of the coefficient of determination variance (r2) is 0.173, which means that the Understanding of the couples About Anger According to the Book of Proverbs contributes to the Marriage Harmony. So that the better the understanding of the couples about anger Based on the Book of Proverbs, the better the interpretation of the Marriage Harmony Leader of Bethel Tabernacle Church of Christ Alfa Omega in the Central Java Region Abstrak Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pemahaman pasangan tentang kemarahan berdasarkan Kitab Amsal terhadap pernikahan pemimpin Gereja Tabernakel Betel Kristus Alfa Omega (GBT KAO) di Wilayah Jawa Tengah. Responden dari penelitian ini adalah 150 pasangan pemimpin KAO GBT di Jepara, Pati, Semarang, Temanggung, Salatiga dan Solo. Berdasarkan uji korelasional menggunakan rumus Pearson, koefisien korelasinya adalah 0,417 dengan signifikansi (Nilai-P) 0,000. Ini menyatakan bahwa ada pengaruh positif dan kuat antara pemahaman pasangan tentang kemarahan berdasarkan buku amsal tentang keharmonisan pernikahan pemimpin Gereja Tabernakel Bethel Christ Alfa Omega di wilayah Jawa Tengah. Hasil regresi antara variabel X dan Y juga dapat dilihat bahwa besarnya koefisien determinasi varians (r2) adalah 0,173, yang berarti bahwa pemahaman pasutri tentang kemarahan berdasarkan Kitab Amsal berkontribusi pada keharmonisan pernikahan. Sehingga semakin baik pemahaman pasangan tentang kemarahan Berdasarkan Kitab Amsal, maka semakin baik interpretasi keharmonisan pernikahan pemimpin Gereja Bethel Tabernakel Kristus Alfa Omega di Wilayah Jawa Tengah.